Emergency remote teaching: The experiences of a public school and a private school in campina grande/PB - Almeida, Ligia Beatriz Carvalho [UNESP]; Mendes, Iasmin Araujo Bandeira; Araujo, Jamila Monteiro (Associacao Pro-Ensino Superior em Novo Hamburgo, 2021)
This paper reports the findings of a qualitative, descriptive research conducted in the context of the COVID-19 pandemic, focusing on its impact on education. Emergency remote education provided by a public school and a private school, located in the city of Campina Grande, PB, were analyzed through class observations and semi-structured interviews. It is, therefore, a comparative study, focusing on the methodological aspects of the observed classes, in order to understand the potential and challenges faced in each reality and the extent to which the educommunicative perspectives of interaction and dialogue were put into practice. Eighth-year classes with their respective mathematics teachers and a manager from each institution took part in this research. Through the data, the conclusion was that the private school easily adapted to the technological context with regard to the technical bias, on the other hand, with regard to the methodology, the online teaching was little dialogic, with content in excess and little student interaction. In public schools, the biggest challenge was the inclusion of students on digital platforms and their lack of attendance, which slows down the fulfillment of curricular content. Such analysis was possible based on studies by theorists such as Freire, 1989), Soares, 2011, 2019) and Citelli, 2019From this research, it is possible to perceive the urgency of including an educommunication professional in the public and private schools so that he can contribute to meet the challenges mentioned.
Ensino remoto emergencial: as experiencias de uma escola publica e de uma particular em campina grande/PB
Keywords: Educommunication; Elementary School; Emergency Remote Education; Mathematics; Paraiba